Disease burden comparison and associated risk factors of early- and late-onset neonatal sepsis in China and the USA, 1990–2019 - Chengyue Zhang; Lianfang Yu; Xiaoming Pan; Yuwei Lu; Kaiyu Pan (Global Health Action)
Background The morbidity and mortality rates of neonatal sepsis are high, with significant differences in risk factors and disease burden observed between developing and developed countries. Objective To provide evidence to support recommendations on improving public health policies using a comparative systematic analysis of the disease burden. Methods Using data from the Global Burden of Disease Study 2019, the prevalence and incidence of early- and late-onset neonatal sepsis and the disability-adjusted life years (DALYs) due to both countries in both China and the United States of America (USA) were assessed. Furthermore, the DALYs and summary exposure values for the primary risk factors (short gestation and low birthweight) were analysed. Joinpoint regression models were used to analyse temporal trends in epidemiological indicators of neonatal sepsis. Results Between 1990 and 2019, the incidence and prevalence of neonatal sepsis demonstrated a significant upwards trend in China, whereas both were largely stable in the USA. A decreasing trend in the DALYs due to neonatal sepsis caused by short gestation and low birthweight in both sexes was observed in both countries, whereas a fluctuating increasing trend in years lived with disability was observed in China. Conclusions The aim of the Chinese public health policy should be to control risk factors, learning from the advanced health policy planning and perinatal management experiences of developed countries.